VIRTUAL BOX CAMPAIGN STRATEGY FOR THE GIBRAN-TEGUH CANDIDATE PAIR DURING PANDEMIC IN THE 2020 SURAKARTA ELECTIONS - Laila Istiana Diana Savitri (LUGAS Jurnal Komunikasi, 2022)
The aims of this research are to find out the branding campaign, segmenting, factors that are supporting and inhibiting throughout the Gibran-Teguh candidate pair virtual box campaign during pandemic in the 2020 Surakarta Elections.This type of research is normative legal research. The data obtained from library will be analyzed qualitatively by sorting and selecting the data obtained, then compiled systematically and studied using deductive thinking methods, then conclusions are drawn to answer the problems contained in the research.This research uses qualitative methods, data analysis using data reduction, Data Display and Conclusions Drawing. In the data validity technique, triangulation of sources is used, namely the sources including the success team, the community, and members of the Surakarta Election Supervisory Committee. These sources are then described and categorized, that later on can create the conclusions.The results showed that the branding carried out by the team and the candidate pair using virtual box succeeded in influencing the people in Surakarta. Several segmenting points were carried out by the Gibran-Teguh candidate pair, by knowing and understanding the political competition map in the 2022 Surakarta Elections. Factors supporting the virtual box campaign of the Gibran-Teguh candidate pair includes virtual box media, personal brands, campaign funds, campaign social networks, campaign teams and so on. Meanwhile, factors inhibiting the virtual box campaign are political dynasties, black propaganda, and Covid-19 conditions. The pandemic has caused a lack of free mass gatherings, so that an efficient campaign strategy is needed during the pandemic.